Efeitos da Implementação da Sistematização da Assistência de Enfermagem nos Enfermeiros de uma Instituição de Saúde Pública - Lisboa, Geny da Silva Nascimento (2005)
The present study had as an objective to investigate the opinion of the nurse on the Systematization of the Nursing Assistance, verify the effect of the Systematization of the Nursing Assistance on the organization of the work of the nurse and identify if the Implementation of the Systematization of the Nursing Assistance causes psychical suffering in these professionals. It is about a qualitative research, carried through with 22 nurses who act in a public institution of health of the great ABCD, in the State of São Paulo. Semi structuralized interviews has been used, by means of recording of the depositions. The analysis of the data was carried through trying to apprehend the representational content of the effect of the Implementation of the Systematization of the Nursing Assistance on the Nurses. The categories of analysis under the influence of the SNA on the citizens had been: a)knowledge of the SNA: it has knowledge and it has little knowledge; b)opinion about the SNA: favorable and partially favorable; c)development of the SNA in the context of the work: it occurs partially and it does not occur; d)influence of the Implementation of the SNA on the performance of the tasks: it affects and it does not affect; e)occurrence of psychical suffering in the Implementation of the SNA: it has and it does not have direct expressions of psychical suffering. The data has disclosed that the effect of the Implementation of the Systematization of the Nursing Assistance on the Nurses causes psychical suffering, as a result of the inadequate conditions of the work to promote the Systematization of the Nursing Assistance.